2022
DOI: 10.3390/su14137786
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study on Ethical Buyer Behavior towards Cruelty-Free Cosmetics: What Consequences for Female Leadership Practices?

Abstract: This study extends the theory of planned behavior model and examines the humane factors (altruism, environmental knowledge, personal appearance concerns, attitude, perceived behavioral control, and subjective norms) that shape attitudes and buyer behavior toward cruelty-free cosmetics and the consumer characteristics that reflect their behavior toward such products. Recent global occurrences have affected human behavioral patterns, namely, the COVID-19 pandemic, which we aim to study. Has behavior changed to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 58 publications
(76 reference statements)
0
11
0
Order By: Relevance
“…Attitude Among the TPB variables, attitude was the most frequently demonstrated predictor of GCPI and GCPB (27 times). A variety of attitudes were assessed in the surveyed literature, which ranged from the general attitude to green cosmetics consumption [2,3,9,[13][14][15][16][17]32,35,36,41,42,46,48,52,53,57] to other minor attitudes such as hedonic and utilitarian attitudes [58], the attitude toward cannabis-based skincare cosmetics [22], and the attitude toward cruelty-free cosmetics [20,40].…”
Section: Theory Of Planned Behavior (Tpb)-related Themesmentioning
confidence: 99%
See 4 more Smart Citations
“…Attitude Among the TPB variables, attitude was the most frequently demonstrated predictor of GCPI and GCPB (27 times). A variety of attitudes were assessed in the surveyed literature, which ranged from the general attitude to green cosmetics consumption [2,3,9,[13][14][15][16][17]32,35,36,41,42,46,48,52,53,57] to other minor attitudes such as hedonic and utilitarian attitudes [58], the attitude toward cannabis-based skincare cosmetics [22], and the attitude toward cruelty-free cosmetics [20,40].…”
Section: Theory Of Planned Behavior (Tpb)-related Themesmentioning
confidence: 99%
“…Several studies (e.g., [2,8,14,15,20,32,35,36,44]) established perceived behavioral control as a significant predictor of GCPI and GCPB. However, other studies reported an insignificant relationship [16,40].…”
Section: Perceived Behavioral Controlmentioning
confidence: 99%
See 3 more Smart Citations